Human-in-the-Loop Formation-Containment Control for Multiagent Systems: An Observer-Based Distributed Unknown Input Reconstruction Method - Ma, Li; Zhu, Fanglai; Zhao, Xudong (IEEE transactions on control of network systems, 2023)
This paper studies the human-in-the-loop time-varying formation-containment tracking (TVFCT) control problem of general linear multiagent systems (MASs). The MASs consist of a non-autonomous tracking leader, multiple formation leaders and followers, and all agents are subject to unknown disturbances. A human operator is deployed to supervise and regulate the entire team by sending a command signal to the tracking leader. The control input of the tracking leader should be combined with the human operator but not available to other agents. First, a local observer associated with each agent is constructed to provide asymptotic state estimation, in which the observer error system is disturbance-free. Also, interval observers are established for the neighborhood TVFCT errors, where the disturbance of the current agent is aggregated with the disturbances and input signals of its neighbors into an unknown input. Meanwhile, a distributed asymptotic unknown input reconstruction (UIR) mechanism is proposed that decouples the control input of the current agent. The consequent human-in-the-loop TVFCT control protocol is designed by combining the local observer and distributed UIR scheme. Finally, the theoretical results are verified in multi-robot formation-containment control.